Constraining the pressure-temperature evolution and geodynamic setting of UHT granulites and migmatitic paragneisses of the Gruf Complex, Central Alps - Oalmann, Jeffrey (2021)
Thermodynamic modeling of compositionally mapped microdomains and whole-rock compositions is used to constrain the pressure–temperature (P–T) evolution of sapphirine granulites and migmatitic paragneisses from the Gruf Complex of the Central Alps. The P–T paths and conditions estimated from granulite microdomains and whole-rock compositions are consistent with one another, indicating that the estimates from both types of compositions are accurate. The sapphirine granulites were heated to ultra-high temperature conditions of 900–1000 °C and 7.0–9.5 kbar as they were decompressed from ca. 800 °C and 9–12 kbar, resulting in garnet breakdown. In a subsequent step, nearly isothermal decompression led to the development of cordierite-bearing coronae and symplectites. By ca. 27 Ma, the sapphirine granulites had been exhumed to the midcrustal level of the migmatitic paragneisses, which were undergoing peak metamorphism at ca. 675–750 °C and 5–7 kbar. These results are consistent with a geodynamic model that invokes heat advection to the lower crust closely following the continental-subduction (ultra-high pressure) stage of the Alpine orogeny. The most plausible geodynamic model consistent with the results of this study is breakoff of a southward subducting lithospheric slab, resulting in asthenospheric mantle flow.